Análise da influência do porte, entre outros fatores, sobre vários aspectos da competitividade de manufaturas de calçados masculinos - Silva, Sérgio Evangelista (Universidade Federal de São Carlos, 2007)
This thesis has the purpose of analyzing the size and other factors of male shoes manufactories (denominated) MCMs about their relationship with externals elements (macro e microeconomic elements), on the configuration of internal elements (managerial system, Manufacturing, Sales and Marketing, Research and Development (R&D)) and reference elements (their performance attributes and performance objectives). This research uses the qualitative approach aiming the study of six big size MCMs and fourteen small size ones, all located in Franca, known as a leader cluster in male shoes manufacturing. The method used in this research was the multiple case studies and the related data were collected by interviews applied in these firms. Among the main results, it can be noticed that the size is an extreme important factor on determining the relationship of the MCMs with external, internal e reference elements. However, there were identified many other factors that play a relevant role in the MCMs competitiveness. Therefore, the main contributions of this research are: a wide review on competitiveness literature and proposal of its four perspectives; the proposal of a general model of firm relationship with the external, internal and reference elements; distinction between performance objective and performance attribute; a wide view of male shoes industry organization and the way its firms work; application of the general model of the firm relationship with the external, internal and references elements to the shoe industry
Keywords: Competitividade; Estratégia competitiva; Indústria do calçado; Competitiveness; Competitive Strategy; Footwear Industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO